2016
DOI: 10.1016/j.jaci.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Household almond and peanut consumption is related to the development of sensitization in young children

Abstract: those without S aureus colonization (70% vs 48%, P < .0001). Diagnostic code for anaphylaxis, prescription for an epinephrine autoinjector, or both were also found to be significantly more prevalent in patients with S aureus colonization versus those without S aureus colonization (53% vs 44%, P 5 .04; see Tables E1 and E2 in this article's Online Repository at www.jacionline.org).These data suggest there is an association between S aureus colonization and food allergy to peanut, egg white, and cow's milk in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Household peanut consumption was ten times higher in households with infants with peanut allergy vs children with egg allergy without peanut allergy but was only 3 times higher in non‐atopic controls, highlighting that household peanut consumption was more likely to be associated with peanut allergy in high‐risk children . Household peanut consumption and peanut sensitization have also been associated in other studies . Peanut antigen in the infant's bed dust and play‐area‐dust is highly positively correlated with household peanut consumption and stimulates basophils from peanut allergic children, thus has the potential to also sensitize individuals …”
Section: Introductionmentioning
confidence: 69%
“…Household peanut consumption was ten times higher in households with infants with peanut allergy vs children with egg allergy without peanut allergy but was only 3 times higher in non‐atopic controls, highlighting that household peanut consumption was more likely to be associated with peanut allergy in high‐risk children . Household peanut consumption and peanut sensitization have also been associated in other studies . Peanut antigen in the infant's bed dust and play‐area‐dust is highly positively correlated with household peanut consumption and stimulates basophils from peanut allergic children, thus has the potential to also sensitize individuals …”
Section: Introductionmentioning
confidence: 69%
“…A recent study reported that household consumption of almond and peanut was related to development of sensitization to peanuts [ 28 ].…”
Section: Prevalencementioning
confidence: 99%
“…A published letter to the editor showed that a clear relationship was found between nut consumption by relatives and IgE-mediated sensitization in children Ͻ18 months old. 22 In our study, we did not assess the age of diagnosis, but, in 40% of our restricted homes, the eating practices of family members changed after receiving a peanut allergy diagnosis. This could explain why individuals in our study had a peanut allergy despite no current consumption in the home.…”
Section: Discussionmentioning
confidence: 97%